The Professional Agency Narrative—Conceptualizing the Role of Professional Knowledge in Frontline Work. (12th June 2021) - Cecchini, Mathilde; Harrits, Gitte Sommer
Abstract: The street-level bureaucracy literature teaches us that frontline workers draw on both policy logics and social, cultural, and personal logics in their work. This has been conceptualized as the state agency narrative and citizen agency narrative, and it is both well documented and well theorized. However, the literature on street-level bureaucracy and frontline work is remarkably silent on how to understand the role of professional knowledge in frontline work. In this article, we seek to fill this gap by theorizing and empirically demonstrating how frontline work is characterized by what we call a professional agency narrative centering on problem solving and the use of knowledge on "what works." We do so through in-depth qualitative analyses of data from two empirical studies on frontline work in schools. The first is an interview study consisting of 42 semi-structured interviews with Danish preschool and school teachers on the topic of prevention of social and health risks. The second study is an ethnographic study consisting of more than 500 h of observation, two focus groups with teachers and seven semi-structured interviews with teachers on the topic of health risk prevention in Danish schools. Based on the analysis of this rich qualitative data, we develop the concept of the professional agency narrative and discuss how this concept can contribute to the broader literatures on street-level work and the management of street-level work.